As práxis, os saberes e a pessoa do docente refletido no saber-fazer pedagógico - Prade, Maria Berenice Koetz (2007)
This research aims at identifying the web of factors interfering with students' adherence to a state school of Porto Alegre, Brazil. To do so, it focuses on understanding the process established between the subjects, actions and backstage of teaching practices, recognizing the school as a democratic space that aims to ascertaining the socialization of universal knowledge to new generations. In this context, it investigates the situations contributing for the students lack of interest for pedagogical activities. In this sense, it casts a look on the teachers actions during the organization of their professional life, their personal relationship with students and their pedagogical know-how. The plural knowledge that is part of teaching praxis and that interact with the students schooling success has been considered. Taking into consideration that the postmodern world has constant innovations in all areas of human development, which challenges educational practices, knowledge and application of processes to make teaching more pleasant, playful and contextualized are crucial. In this sense, it analyzes the school spaces and management, as an attempt to stress the school s weak points and signal the challenges to transform it into a pool of knowledge, professional growth for teachers and students insertion into new technologies and challenges of the working world.